2013
DOI: 10.7150/ijms.6244
|View full text |Cite
|
Sign up to set email alerts
|

Determining Timing of Hepatectomy for Colorectal Cancer with Distant Metastasis According to Imaging-Based Tumor Shrinkage Ratio

Abstract: Background: The optimal timing of surgical resection of liver metastasis remains controversial, and guidelines regarding the upper limits of operative indications have not yet been defined. Surgical indication for metastasis from colorectal cancer (CLM) based on results of preoperative chemotherapy and RNF8 was investigated. Methods: Differences in CLM size on CT were evaluated as shrinkage rate/day by dividing tumor shrinkage rates by the interval in days between CT. Levels of RNF8 of resected colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…On this basis, cytoreduction of the disease may prolong OS and PFS times. We recently reported that the overall rate of tumor shrinkage was highest during the first 50 days after the start of therapy and gradually decreased over the next 210 days subsequent to plateauing at 105 days ( 33 , 34 ). The present results indicated that the effect of anti-EGFR monoclonal antibodies plus FOLFOX on tumor size is achieved at around 3 months (6–8 courses).…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, cytoreduction of the disease may prolong OS and PFS times. We recently reported that the overall rate of tumor shrinkage was highest during the first 50 days after the start of therapy and gradually decreased over the next 210 days subsequent to plateauing at 105 days ( 33 , 34 ). The present results indicated that the effect of anti-EGFR monoclonal antibodies plus FOLFOX on tumor size is achieved at around 3 months (6–8 courses).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to its tumor suppressive functions, RNF8 may also play positive roles in tumor progression. The mRNA level of RNF8 was found to be higher in colorectal cancer than in normal tissues [77], which suggests RNF8 may promote the survival of certain cancers. The silencing of RNF8 by specific siRNA in nasopharyngeal cancer (NPC) cells enhanced the sensitivity of NPC cells to irradiation.…”
Section: Tumorigenesis and Cancer Progressionmentioning
confidence: 94%
“…We reported previously that the tumor shrinkage effect reaches a plateau in about 100 days based on the radiological response of tumor shrinkage and drug-resistance mechanisms [16] [17]. Based on this evidence, including the ndings of the past trials [18] [19] [20], following the approval of a multidisciplinary team, six cycles of oxaliplatin-based PC with molecular targeted drug therapy were administered to patients with borderline or unresectable CRLM that was in extensive contact with the root of the major hepatic veins or Glisson's capsules or who had insu cient residual liver volume.…”
Section: Treatment Strategies For Crlmmentioning
confidence: 99%